Doping properties of MoS2/ZnO (0001) heterojunction ruled by interfacial micro-structure: From first principles. (February 2015) - Liang, Pei; Tai, Bo; Shu, Haibo; Shen, Tao; Dong, Qianmin
Abstract: The stability and the electronic properties of a monolayer MoS2 adsorbed on the O-terminated ZnO (0001) have been investigated by using the first-principles approach. By changing the surface of ZnO substrate, we find that the conductivity of ultrathin semiconducting LTMDs changes from n - to p -type conducting depending on the microstructure of the ZnO surface. We find that MoS2 /ZnO based on clean ZnO substrate shows p -type conductivity; while the MoS2 /ZnO based on ZnO with coverage of 1/2 monolayer of hydrogen becomes an intrinsic semiconductor, the MoS2 /ZnO based on ZnO with coverage of one monolayer of hydrogen turns into n -type semiconductor. This can pave the way for a new strategy in the design of two-dimensional devices, where the electronic properties of the channel are engineered by manipulating those of the substrate. Highlights: Interfacial microstructure ruled doping properties of MoS2 /ZnO heterostructure have been investigated. By change the passivation ratio of the ZnO surface the doping character can change from n-type to p-type.